2018
DOI: 10.1140/epjds/s13688-018-0161-9
|View full text |Cite
|
Sign up to set email alerts
|

Are the different layers of a social network conveying the same information?

Abstract: Comprehensive and quantitative investigations of social theories and phenomena increasingly benefit from the vast breadth of data describing human social relations, which is now available within the realm of computational social science. Such data are, however, typically proxies for one of the many interaction layers composing social networks, which can be defined in many ways and are typically composed of communication of various types (e.g., phone calls, face-to-face communication, etc.). As a result, many s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…However, there are some limitations to our work. For example, the conceptual design of the multi-agent model seriously lacks justifications and grounding based on empirical data [ 41 ]. In future work, we will collect new empirical data to improve the simulation result’s accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some limitations to our work. For example, the conceptual design of the multi-agent model seriously lacks justifications and grounding based on empirical data [ 41 ]. In future work, we will collect new empirical data to improve the simulation result’s accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers understand reasonably well that the disease spreads in places where people spend a lot of time face-to-face, such as care homes, hospitals and restaurants [1][2][3] . Duration of contact, physical proximity and environmental conditions are the main factors.…”
Section: Close Contactmentioning
confidence: 99%
“…As promising as this proposed approach sounds, it is critical to bear in mind that social networks are "complex animals" with multiplex or multilayer net works. Data scientist Alain Barrat and his collaborators recently demonstrated that different layers of a social network do not always con vey the same information [8]. Hence, the proposed approach of introducing perturbations may be chal lenging to implement in an online social network replete with human flaws and foibles, unlike a comparatively straightforward robotic swarm interaction network.…”
Section: The Potential Of Perturbationsmentioning
confidence: 99%